2009
DOI: 10.4269/ajtmh.2009.08-0175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peridomestic Environments on Repeated Infestation by Preadult Aedes aegypti in Urban Premises in Nha Trang City, Vietnam

Abstract: Abstract. To determine the effect of peridomestic environments on Aedes aegypti infestation in urban premises, we conducted two consecutive surveys in the hot-dry and cool-wet seasons. Most Ae . aegypti pupae (79%) were recovered from premises where preadult forms (larvae and/or pupae) had been detected in both surveys. Hence, repeated infestation appears to be a useful parameter to identify premises associated with a high potential risk of dengue transmission. Multivariate analysis revealed that not only the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
3
18
0
Order By: Relevance
“…aegypti immatures is that they can differ dramatically between local areas. This has been demonstrated in a series of multicountry studies (Focks and Alexander 2006, Tun-Lin et al 2009, Arunachalam et al 2010 and also is evident when comparing the results of studies focusing on individual geographical areas (Moore et al 1978;Winch et al 1992;Kittayapong and Strickman 1993;Focks and Chadee 1997;Danis-Lozano et al 2002;Pinheiro and Tadei 2002;Arredondo-Jimenez and Valdez-Delgado 2006;Barrera et al 2006Barrera et al , 2008Bisset et al 2006;Lenhart et al 2006;Midega et al 2006;Morrison et al 2004Morrison et al , 2006Romero-Vivas et al 2006;Chadee et al 2007Chadee et al , 2009Hammond et al 2007;Koenraadt et al 2007;Maciel-de-Freitas et al 2007; Barbazan et al 2008;Manrique-Saide et al 2008;Troyo et al 2008;David et al 2009;Garelli et al 2009;Lambdin et al 2009;Tsuzuki et al 2009;Kamgang et al 2010). Furthermore, the most productive container types can change over the year, especially in settings with dry and wet seasons where the importance of containers Þlled by rain, relative to those Þlled by human action, may vary over the year in response to the seasonal rainfall patterns (Pinheiro and Tadei 2002, Lenhart et al 2006, RomeroVivas et al 2006, Maciel-de-Freitas et al 2007…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…aegypti immatures is that they can differ dramatically between local areas. This has been demonstrated in a series of multicountry studies (Focks and Alexander 2006, Tun-Lin et al 2009, Arunachalam et al 2010 and also is evident when comparing the results of studies focusing on individual geographical areas (Moore et al 1978;Winch et al 1992;Kittayapong and Strickman 1993;Focks and Chadee 1997;Danis-Lozano et al 2002;Pinheiro and Tadei 2002;Arredondo-Jimenez and Valdez-Delgado 2006;Barrera et al 2006Barrera et al , 2008Bisset et al 2006;Lenhart et al 2006;Midega et al 2006;Morrison et al 2004Morrison et al , 2006Romero-Vivas et al 2006;Chadee et al 2007Chadee et al , 2009Hammond et al 2007;Koenraadt et al 2007;Maciel-de-Freitas et al 2007; Barbazan et al 2008;Manrique-Saide et al 2008;Troyo et al 2008;David et al 2009;Garelli et al 2009;Lambdin et al 2009;Tsuzuki et al 2009;Kamgang et al 2010). Furthermore, the most productive container types can change over the year, especially in settings with dry and wet seasons where the importance of containers Þlled by rain, relative to those Þlled by human action, may vary over the year in response to the seasonal rainfall patterns (Pinheiro and Tadei 2002, Lenhart et al 2006, RomeroVivas et al 2006, Maciel-de-Freitas et al 2007…”
mentioning
confidence: 75%
“…Several previous studies have compared productive container types during dry and wet parts of the year (Pinheiro and Tadei 2002, Lenhart et al 2006, RomeroVivas et al 2006, Maciel-de-Freitas et al 2007, Barbazan et al 2008, Troyo et al 2008, Chadee et al 2009, Lambdin et al 2009, Tsuzuki et al 2009). Not surprisingly, a trend emerges from these studies toward containers Þlled by human action being more important producers of Ae.…”
Section: Discussionmentioning
confidence: 96%
“…A limitation of the study was that larvae were collected from used tires only [43]. The results of other studies revealed a variety of larval habitats throughout urban and rural and north to south gradients in Vietnam [12, 4850]. The way in which People stored water affected mosquito larval occurrence.…”
Section: Spatial Distribution Of Dengue Vectorsmentioning
confidence: 99%
“…The main mosquito vector ( Ae. aegypti ) typically breeds well in human-made container habitats such as water storage jars in and around human settlements including those in dense urban areas [2],[3]. This breeding behavior stands in contrast to most Anopheles species (the vector for malaria), which usually avoid urban ecosystems, leading to a low malaria risk in cities [4].…”
Section: Introductionmentioning
confidence: 99%